Phytochemical analysis of ethanolic Psidium guajava leaves extract using GC-MS and LC-MS - RISA NURSANTY; KHAIRUL NAIM BIN MD PADZIL; NUR ISTI’ANAH BINTI RAMLI; NOR AINY MAHYUDIN; AHMAD HANIFF BIN JAAFAR; YAYA RUKAYADI (Society for Indonesian Biodiversity, 2023)
Abstract. Nursanty R, Padzil KNBM, Ramli NIB, Mahyudin NA, Jaafar AHB, Rukayadi Y. 2023. Phytochemical analysis of ethanolic Psidium guajava leaves extract using GC-MS and LC-MS. Biodiversitas 24: 2723-2732. Psidium guajava L. is well known as guava and has been used traditionally as a medicinal plant for a variety of ailments all over the world, especially in infusions and decoctions for oral and topical use. Every part of this plant has been used for treating stomachache and diarrhea in many countries. Other reported uses include dermatitis, sores, epilepsy, and wounds.Medicinal plants have an important role in complementary and alternative medicine because they produce various natural compounds with high therapeutic properties. Many researchers report that the major chemical composition of this plant includes tannins, phenols, flavonoids, saponins, carbohydrates, alkaloids, sterols, terpenoids, and phenolic compounds. The aim of this study is to identify the volatile and non-volatile compounds in ethanolic P. guajava leaves extract. This study aimed to identify phytochemical compounds in P. guajava leaves extract. The main volatile compounds identified using GC-MS were pyrogallol, ?-copaene, caryophyllene, aromadendrene, ?-humulene, alloaromadendrene, ?-muurolene, ?-selinene, ?-selinene, ?-muurolene, ?-bisabolene, ?-bisabolene, (-) globulol, caryophyllene oxide, ?-muurolol, and epiglobulol. Based on LC-MS analysis, a number of non-volatile compounds such as flavonoids; apigenin 7-?-?-D-glucuronopyranoside, quercetin, luteolin 7-O-glucuronide, naringenin 4?-O-glucopyranoside, and myrecitin along with phenolic derivatives such as quinic acid, catechin, and epigallocatechin (4?,8)-gallocatechin were tentatively identified.